Istorija nauki o fiziceskoj kul'ture i sporte: teoretiko-metodologiceskie aspekty - Vorozko, Ju. B. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The article is devoted to the history-logical and historiographical analysis of the theoretical methodological problems of the periodization, the evolution of scientific knowledge, methodology, contradictions and the category "law" in the context of the history of the science about physical culture and sports.